Komunikasi interpersonal antara tim carl’s jr. Kertajaya surabaya dalam upaya meningkatkan pelayanan dengan pelanggan - Putri, Eka Okta Viana; Putro, Raden Hartopo Eko (Soetomo Communication and Humanities, 2020)
this study uses qualitative methods, using the interpersonal communication theory of Josep De Vito. The purpose of this research is to know how Interpersonal communication between Team Carl's Jr. Kertajaya with customers can improve the assessment. In the service undertaken by team Carl's Jr. With customers always involve interpersonal communication to facilitate the work process as well to achieve the desired objectives. This research shows that interpersonal communication involves several aspects of achieving attitude change, opinion change, behavior change, and social change. Some of these aspects occur in several stations that are in service ranging from cashier, dining team, marketing, as well as supervisors with customers. Interpersonal communication here is used by the team to get the ease of reaching the goal, the cashier to upselling, the marketing team in introducing new products as well as facilities for customer loyalty, dining teams to make customers more comfortable, as well as supervisors in ensuring customer convenience during transactions. So that good interpersonal communication will generate customer satisfaction and help improve the service.Keywords: interpersonal communication; service; satisfaction; valuation; feedback.